Vitex agnus castus effects on hyperprolactinaemia - Puglia, Lídice Tavares; Lowry, Jean; Tamagno, Gianluca (Frontiers in Endocrinology, 2023)
Background: Vitex agnus castus (VAC), also known as chaste tree, is a plant from the Mediterranean area, Crimea, and central Asia. Its fruit has been used for more than 2500 years as phytotherapic agent. In the last century, VAC has been mostly used for the treatment of premenstrual syndrome (PMS), menstrual irregularities, fertility disorders, and symptoms of menopause. Since some degree of hyperprolactinaemia may be observed in patients with such disorders, VAC effects on hyperprolactinaemia have been assessed in a small number of studies and in some patient series or single case reports. It has been postulated that the diterpenes contained in VAC extract may interact with dopamine D2 receptors (D2R) and inhibit prolactin release via dopamine D2R activation in the anterior pituitary. Most of the published papers focus on the use of VAC for the management of PMS or infertility. However, due to its action on D2R, VAC could have a role in the treatment of mild hyperprolactinaemia, including patients with idiopathic hyperprolactinaemia, microprolactinoma, drug-induced hyperprolactinaemia, or polycystic ovary syndrome.Methods: We have reviewed and analyzed the data from the literature concerning the use of VAC extracts in patients with hyperprolactinaemia.Results: Some evidence suggests a possible role of VAC for the management of hyperprolactinaemia in selected patients, though in a inhomogeneous way. However, there are not any large randomized controlled trials supporting the same and the precise pharmacological aspects of VAC extract in such a clinical setting still remain obscure.Conclusions: It appears that VAC may represent a potentially useful and safe phytotherapic option for the management of selected patients with mild hyperprolactinaemia who wish to be treated with phytotherapy. However, larger studies of high quality are needed to corroborate it.